The Other Side of the Street - Taylor-Mitchell, Laurie (Social justice, 2005)
Part of a special issue on the many faces of violence. An interview with sociologist Stan Cohen, who has spent his life analyzing and opposing injustice and inhumanity. Topics discussed include torture, social control, and people's extraordinary capacity for denial.